Sustainable Maintenance Strategy for Wood Windows Defects - Eren, Özlem; Okumuş, Emine Merve (Sakarya Üniversitesi, 2020)
Regular maintenance and repair of window systems in the existing building stock provide both resource and energy savings. While planning the maintenance strategy of window systems that offer benefit in terms of two different aspects, first of all, the possible damage types should be known. Then, what is the damage to the scope of this study? The question was investigated, and the causes and types of defects in the wooden windows were listed. The proposed maintenance planning method is based on 5 tools. The tools that can be used for maintenance planning are listed in the literature. First, the defect levels of the wood windows were specified and then the AHP method was used to select among the alternative maintenance according to the severity of the defect. The study was planned according to the 6 Sigma tool. Firstly, the causes of the defects were investigated and then these defects were evaluated by assigning numbers to each defect by experts. Finally, the AHP method was used to select the right alternative among proposed maintenance alternatives according to the level of defects. By using this simple method while choosing the window maintenance strategy according to the demands, wrong decision-making will be prevented.
Keywords: Maintenance; Wood Window; Defect